Transport Logistics and Simulation Model for Fleet of Drones in a Mass Customization System - Olivares-Chiappa, V (Institute of Electrical and Electronics Engineers Inc., 2017)
This work proposes the use of a fleet of drones (quadcopter/optocopter) inside a production plant of plastic products for the home, in the transport of the materials and components necessary for the personalization of products in the last phases of the production process in a Mass Customization System. A computational tool is designed to configure the fleet to perform certain logistic operations under different operating conditions. It is considered the demand for products (volume and weight), the power and speed of the drones and finally, the distance travelled based on the layout of the plant and transport layout of the drones. The fleet of drones considers a 3D transport space and several structures and configurations have been developed to allow 3D movements. It also analyses the problem of routing of the fleet of drones using several heuristic methods and simulation, whose objective function is to minimize the total cost. An extension of the problem of the traveller seller with capacity and restrictions is analysed (CVRP). Finally, a technological uprising required by the drone transport system is carried out. © 2017 IEEE.